Associated factors affecting the quality of life of the elderly - Özgür Özerdoğan; Buse Yüksel; Merve Çelik; Sibel Oymak; Coşkun Bakar (Turkish Society of Public Health Specialists, 2018)
Objective: The aim of this study was to investigate factors affecting the quality of life of people aged 65 and over, living in the center of Çanakkale province. Method: The sample size in this cross-sectional study was determined as 961. 1001 participants were reached and data was collected using a face-to-face interview technique and questionnaires. Results: Following univariate analyses of the data, it was found that the following variables reduced the EUROHIS scores of the respondents: regretting the past, not accomplishing previous life goals, not being hopeful for the future, experiencing a fall in the last six months, having at least one chronic illness diagnosed by a physician requiring the long-term use of the medication, decrease in income status and dependence on activities within daily life. Conclusions: Longitudinal studies have been initiated, in cooperation with local authorities, in order to improve the quality of life of the elderly. These studies will follow up the biopsychosocial aspects of risk factors which reduce the quality of life of elderly individuals in our study group. Further investigations at the local and national levels will contribute to the implementation of the necessary interventions to address the unique needs of the elderly population.